PENGARUH PENERAPAN METODE POSTER COMMENT TERHADAP PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN PEMBIAKAN TANAMAN PADA KELAS X AGRIBISNIS TANAMAN DAN HOLTIKULTURA (AG) DI SMK NEGERI 4 GOWA - Waode Nurul Hasanah; Lahming Lahming; Muhammad Rais (Jurnal Pendidikan Teknologi Pertanian, 2022)
The purpose of this class action research was to determine the effect of Poster Comment method on the learning achievement of the X AG class of 4 gowa State Vocational High Schools. This type of research is classroom action research conducted in two cycles. In the first cycle there were two meetings and in the second cycle there were two meetings. The research subjects were all students of class X AG as many as 30 students. Data analysis techniques use quantitative and qualitative data. Based on the results of the study, it can be concluded that the use of Poster Comment method can improve the learning outcomes of class X AG student of State Vocational School 4 Gowa. Improvement of student learning achievement is measured from cycle one evaluation test and cycle two.